Tahir dalam Al-Qur’an (Analisis Komparatif Tafsir Ruh Al-Ma’any dan Mafatih Al-Ghaib) pada Surat Al-Muddassir dan Al-Hajj - Razhak, Abdul; Norfaridatunnisa, Norfaridatunnisa; Mahfuz, Taufik Warman (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2024)
The purpose of this research is to describe tahir in the Qur'an (comparative analysis of the tafsir of the spirit of al-ma'any and mafatih al-ghaib). The research method used in this study is a literature study with a qualitative approach. The data used in this study is the holy book of the Qur'an, precisely in Surah al-Muddassir and Surah Al-Hajj along with the interpretation of the spirit of al-Ma'any by Mahmud Al-alusi and Mafatih al-Ghaib by Imam Fakhruddin Ar-Razi. The results of this study show that Tafsir Mafatih Al-Ghaib to understand the meaning of purification with various kinds of discussions according to the situation. Meanwhile, the Tafsir Ruh Al-Ma'any emphasizes that the command to purify oneself from reprehensible morals.